Datacom equipment power trends and cooling applications (ASHRAE datacom series, 2012)
"Gives data center facility designers and manufacturers a clear understanding of their facilities' design needs and allows them to accurately predict the equipment loads their facilities will need to accommodate. Also includes air and liquid cooling options that may be considered"--